2016
DOI: 10.1021/acs.jpclett.6b02248
|View full text |Cite
|
Sign up to set email alerts
|

Chemisorption of Hydroxide on 2D Materials from DFT Calculations: Graphene versus Hexagonal Boron Nitride

Abstract: Recent nanofluidic measurements revealed strongly different surface charge measurements for boron-nitride and graphitic nanotubes when in contact with saline and alkaline water. 1,2 These observations contrast with the similar reactivity of a graphene layer and its boron nitride counterpart, using Density Functional Theory (DFT) framework, for intact and dissociative adsorption of gaseous water molecules. Here, we investigate, by DFT in implicit water, single and multiple adsorption of anionic hydroxide on sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
89
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 32 publications
15
89
1
Order By: Relevance
“…This implies two membrane properties: First, the limited passage of ions is controlled by an efficient size exclusion mechanism. Second, the membrane can effectively block the penetration of Cl − ions, which might be related to a negative charged surface originated from the adsorption of anionic species such as hydroxide on the membrane surface . Figure d compares the impedance of a sealed Si chip, a CNM, and an open aperture.…”
Section: Ion Transport Through a Single Channel At 1 M Kclmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies two membrane properties: First, the limited passage of ions is controlled by an efficient size exclusion mechanism. Second, the membrane can effectively block the penetration of Cl − ions, which might be related to a negative charged surface originated from the adsorption of anionic species such as hydroxide on the membrane surface . Figure d compares the impedance of a sealed Si chip, a CNM, and an open aperture.…”
Section: Ion Transport Through a Single Channel At 1 M Kclmentioning
confidence: 99%
“…Second, the membrane can effectively block the penetration of Cl − ions, which might be related to a negative charged surface originated from the adsorption of anionic species such as hydroxide on the membrane surface. [19] Figure 2d compares the impedance of a sealed Si chip, a CNM, and an open aperture. One clearly observes the exceedingly high resistance of the CNM even in HCl which has the smallest hydration radius.…”
mentioning
confidence: 99%
“…It is clear that graphene, in the past several years, has dominated the research field of 2D materials as the most promising 2D material . For instance, graphene oxide, as well as its derivatives, have potential applications in organic dyes and in the adsorption of heavy metal ions and arsenate ions.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] It is cleart hat graphene, in the past several years, has dominated the research field of 2D materials as the most promising 2D material. [24][25][26] For instance, graphene oxide,a sw ell as its derivatives, have potentiala pplicationsi no rganic dyes and in the adsorption of heavy metal ions and arsenate ions. Nevertheless, practical applications of graphene are limited by its simple chemistry,a si tc omprises only ac arbon network.…”
Section: Introductionmentioning
confidence: 99%
“…Several theoretical studies have been reported on the twodimensional hexagonal boron nitride (2D h-BN) functionalization using different materials such as H [24], C [25], metals [26,27], functional groups [28][29][30] and organic molecules [17,[31][32][33][34]. In particular we are interested in the functionalization of hydrogenated 2D h-BN by a surface radical reaction that have been previously explored in hydrogenated Si(1 1 1) and (0 0 1) surfaces both experimentally and theoretically [35][36][37][38][39][40][41] in other hydrogenated 2D materials [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%